HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN DEPRESI PADA PASIEN PENYAKIT JANTUNG KORONER (THE CORRELATION BETWEEN SOCIAL SUPPORT AND DEPRESSION IN CORONARY HEART DISEASE PATIENT ) - Chaerunnisa, Syifa Maghfirah; Nuraeni, Aan; Hernawaty, Tati (Journal Nursing Care and Biomolecular, 2017)
Introduction: Depression is a major predictor that decreases the quality of life of patient with Coronary Heart Disease (CHD). One of the factors associated with depression is social support. The relationship between social support and depression in coronary heart disease patients has not been researched yet in Indonesia. This study aimed to determine the relationship beetwen social support and depression in patients with CAD. Method: This research used descriptive correlation method with cross sectional approach. This study was conducted 77 CHD outpatients in one of the government hospital. Data were collected through questionnaires. The first was ENRICHD Social Support Inventory (ESSI) questionnaire with validity value r = 0.036-0.663, p <0.01 and Cronbachs Î± was 0.818. The second is Beck Depression Inventory II (BDI II) questionnaire with validity value r = 0.39 - 0.52, p <0.01 and Cronbachs Î± was 0.90. The data were analyzed by univariate (frequency distribution) and bivariate (rank spearman). Result: The results showed that non depression patients were 72.7% and depression patients were 27.3%, with mild depression (14.3%), moderate (7.8%) and severe (5.2%). Patients with high social support were 64.9% and low social support were 35.1%. The relationship between social support and depression had a p value of 0,000 (r=-0.467). Conclusion: The relationship between social support and depression was moderate and the direction of the relationship was negative. Higher social support caused lower depression. Therefore, social support should be improved in order to avoid depression in patient with CHD.